Christian Calon’s Continental Divide: Chronography of a Continent - Harrod, Ariel (Circuit, 2016)
Christian Calon’s film-installation Continental Divide (2013) asks the question “What is the time of a very large space?”. This paper questions the work itself to see how it tries to answer this question. By putting into resonance Calon’s discourse regarding his work, a description of the materials comprising the work and a descriptive restitution of my own experience of the work, it explores how 1) a singular composing of sound and image, 2) a specific mode of diffusion, and 3) their encounter with a listening subject can render possible the audiovisual experience of “the time of a very large space.”